MOVE STRUCTURE IN NONENGINEERING FINAL PROJECT BACKGROUND - Mohammad Febryanto; Mulyati Khorina; Iis Sulyaningsih; Wastu Kurning Purbandini (IKIP Siliwangi, 2023)
The scientific paper of the final project (TA) of Polban students, especially at the Undergraduate level, has the potential to be published both nationally and internationally. Therefore students must pay attention to the rules in writing scientific work. One rule is to write the background in the introductory chapter. The chapter is a way for the readers to see the contents of the research report. This study aims to investigate the Move and Step in the final project of undergraduate students in nonengineering which are analyzed using the Create a Research Space (CARS) model from Swales and Feak (1994). Qualitative is used because it analyzes the background of the research paper. The researcher investigates phenomenon from the perspective of the participants. There were 173 student final project that were analyzed. Student final project were from non-engineering study programs written in 2022. The result shows that every final project applied Move 1 and Move 3, but slightly Move 2. The Steps in Move 1 were dominated by Step 2 dan Step 3. The Steps used in Move 2 were Step 2 and Step 4, meanwhile in Move 3, Step 1A was found in all the background.